Un perfil de vegetación entre la plata (huila) y el volcán del puracé (1986)
This contribution presents the plant-communities characterized in the trayect between La Plata (Huila) and the crater of the Puracé volcano. The methodology followed in this study is that proposed in the Zurich-Montpellier school (BRAUN-BLANQUET, 1979). The profile of vegetation includs plant-communities of the jungle-type which are pluri-stratified on Ecuatorial and sub-Andean life zones and plantcommunities with a single stratification (upper Paramo belt). In the characterization of the plant-communities described was taken of the physiognomy (the structure as an expression of abiotic conditions).  Dates about plant-density in the arboreal stratum and preliminary characteristics of the soil in some of the places inventaried also are provided.